The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0044624
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Status Is Associated with the Severity of Fibrosis in Women with Hepatitis C

Abstract: IntroductionChronic hepatitis C is the main cause of death in patients with end-stage liver disease. Prognosis depends on the increase of fibrosis, whose progression is twice as rapid in men as in women. Aim of the study was to evaluate the effects of reproductive stage on fibrosis severity in women and to compare these findings with age-matched men.Materials and Methods A retrospective study of 710 consecutive patients with biopsy-proven chronic hepatitis C was conducted, using data from a clinical database o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 28 publications
6
58
0
5
Order By: Relevance
“…One hypothesis is that there may be sex-hormone-specific receptors for many of the immune pathways responsible for HCV natural history. Animal studies have demonstrated estrogen effects hepatic stellate cells that contribute to fibrosis (Shimizu et al, 1999), and human studies have also documented lower rates of fibrosis associated with higher estrogen states (Di Martino et al, 2004; Villa et al, 2012). However, it is also possible that the gender-related differences in spontaneous clearance that we observed could be related to unmeasured differences in the patterns of drinking and/or alcohol exposure among women compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis is that there may be sex-hormone-specific receptors for many of the immune pathways responsible for HCV natural history. Animal studies have demonstrated estrogen effects hepatic stellate cells that contribute to fibrosis (Shimizu et al, 1999), and human studies have also documented lower rates of fibrosis associated with higher estrogen states (Di Martino et al, 2004; Villa et al, 2012). However, it is also possible that the gender-related differences in spontaneous clearance that we observed could be related to unmeasured differences in the patterns of drinking and/or alcohol exposure among women compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the protective role of estrogens in women with chronic liver disease resides in their role in keeping inflammation under control. With menopause, the fall of estrogen levels is accompanied by a rapid increase in the levels of proinflammatory and anti‐inflammatory cytokines . This leads to differential speeds of fibrosis development during fertile and menopausal ages, with women catching up with men in fibrosis progression after menopause .…”
Section: Role Of Age and Gender In The Pretransplant Settingmentioning
confidence: 99%
“…In conclusion, the outcome for both sexes after transplantation is equal for all indications except hepatitis C-induced cirrhosis [4,15,28,36,37,38,39,40,41,42,43]. Women undergoing transplantation because of a hepatitis C-induced cirrhosis have a higher risk for graft loss and rejection and a worse outcome in the case of a recurrent hepatitis C infection [8,15,44,45,46]. The donor's gender does not affect survival or outcome after liver transplantation [4,47].…”
Section: Liver Transplantationmentioning
confidence: 99%